High-quality genome resource of Ustilaginoidea virens (UV2_4G), causal agent of an emerging false smut disease in rice - Bashyal, Bishnu Maya; Yadav, Gaurav Kumar; Parmar, Pooja; Sunani, Sunil Kumar; Aggarwal, Shweta; Gopala Krishnan, S.; Kumar, Atul; Zaidi, Najam Waris; Aggarwal, Rashmi (Scientific Societies, 2023)
Ustilaginoidea virens is the fungal pathogen causing an emerging false smut disease that affects crop yield as well as deteriorates quality of the grains by producing mycotoxins. A high quality genome of U. virens isolate UV2_4G was sequenced using Nanopore and Illumina HiSeq 2,000 sequencing platforms. The total assembled genome of Indian isolate UV2_4G was 35.9 Mb, which comprised 89 scaffolds with N50 of 700,296 bp. A total of 358,697 variants were identified in the genome, out of which 355,173 were SNPs and 3,524 were INDELS. Further, 7,390 SSRs belonging to different repeat types were also identified in the genome. Out of 7,444 proteins predicted, 7,206 were functionally annotated. A total of 1,307 CAZymes, 501 signal peptides, 1,876 effectors, and 2,709 genes involved in host-pathogen interactions were identified. Comparative analysis revealed isolate UV2_4G is distinct with 31 unique clusters and placed distantly in phylogenetic analysis. Taken together, this high-quality genome assembly and sequence annotation resource can give an improved insight for characterizing the biological and pathogenic mechanisms of U. virens.